SIMULATION OF GRAIN PILE SEPARATION IN VERTICAL PNEUMATIC PASSAGE - Yury I. Yermolyev; A. V. Butovchenko; A. A. Doroshenko; S. V. Belov (Advanced Engineering Research, 2012)
The methodology and grain pile pneumatic separation parameters in the vertical pneumatic passage under the specified probabilistic characteristics of the airflow, the grain pile feed into the pneumatic separator, and the terminal velocity probability density of all pile components are described.